Application of environmentally friendly technologies for the management of nanofiltration concentrate from landfill leachate - Guvenc, Senem Yazici; Ozen, Irem; Binici, Miray; Demiroz, Busra; Turk, Oruc Kaan; Can-Guven, Emine; Varank, Gamze (ELSEVIER SCI LTD, 2024)
In this study, the treatability of leachate nanofiltration (NF) concentrate using the modified Fenton process was investigated. The modified Fenton process employs an environmentally friendly oxidant (sodium percarbonate, SPC), an environmentally friendly catalyst (Fe 2 + ), and environmentally friendly activators (electrooxidationultraviolet, EO-UV). The study aimed at enhancing the biological degradability of leachate NF concentrate and was conducted in two stages. In the first stage, the process variables of the SPC/Fe 2 + process were optimized. In the second stage, combined processes were applied under optimum conditions. With the SPC/Fe 2 + process under optimum conditions (pH: 5, SPC dose: 10 mM, Fe 2 + concentration: 50 mM, reaction time: 60 min, pre -catalyst dosing), removal efficiencies of 53.5%, 47.1%, and 61.6% were obtained for chemical oxygen demand (COD), UV 254 , and color, respectively. After optimizing the operational parameters of the SPC/Fe 2 + process, combined processes of EO/SPC/Fe 2 + and UV/SPC/Fe 2 + were applied, and higher pollutant removal efficiencies were achieved with the EO/SPC/Fe 2 + process. Under optimum conditions, removal efficiencies of 75.3%, 80.5%, and 85.6% were achieved for COD, UV 254 , and color, respectively. The first -order reaction rate constant was 0.022 1/ min for the EO/SPC/Fe 2 + process. The biochemical oxygen demand (BOD)/COD, which increased from 0.040 to 0.080 with the SPC/Fe 2 + process, reached 0.455 with the EO/SPC/Fe 2 + process. Additionally, with the EO/SPC/ Fe 2 + process, the biologically degradable COD ratio of leachate NF concentrate increased from 16.7% to 83.5%, and the soluble COD fraction increased from 72.7% to 89.5%.
Keywords: Biodegradability; Combined processes; Leachate nanofiltration concentrate; Modified Fenton; Percarbonate; ZERO VALENT ALUMINUM; WASTE-WATER; ADVANCED OXIDATION; SODIUM PERCARBONATE; AQUEOUS-SOLUTION; FENTON PROCESS; ELECTROCHEMICAL OXIDATION; HYDROGEN-PEROXIDE; DEGRADATION; REMOVAL; Engineering